Characterization of Copper(II) Interactions with Sinefungin, a Nucleoside Antibiotic: Combined Potentiometric, Spectroscopic and DFT Studies - Maria Jaworska; Piotr Lodowski; Ariel Mucha; Wojciech Szczepanik; Gianni Valensin; Massimo Cappannelli; Malgorzata Jezowska-Bojczuk (Bioinorganic Chemistry and Applications)
Interactions between sinefungin and copper(II) ions were investigated. Stoichiometry and stability constants of the metal-free system and two mononuclear complexes present in solution were determined on the basis of potentiometric data analysis. The results were compared to the Cu(II)-ornithine system due to structural similarities between both molecules. Combined spectroscopic and theoretical studies allowed for determination of coordination pattern for the Cu(II)-sinefungin complexes. At acidic pH, copper is bound in “glycine-like” coordination mode, identical with that of ornithine. This involves α-amino group and the carboxyl oxygen. At higher pH, a “bis-complex” is formed by two sinefungin molecules. The second ligand binds in equatorial position displacing two water molecules, what results in the stable {2N,2O} coordination. Both axial positions are supposed to be occupied by N1 nitrogen donors of adenine moiety, what is confirmed by DFT calculations. They interact indirectly with copper(II) through water molecules as the result of dominant syn conformation of purine.